Comparison of Outcomes of Laparoscopic Heller Myotomy Versus Per-Oral Endoscopic Myotomy for Management of Achalasia. Issue 4 (1st October 2017) - Leeds, Steven G.; Burdick, J. S.; Ogola, Gerald O.; Ontiveros, Estrellita
Abstract : Achalasia is a rare disorder that has several treatment options. The gold standard of treatment is a surgical myotomy called a laparoscopic Heller myotomy (LHM). More recently, an endoscopic myotomy has become an option as well, called per-oral endoscopic myotomy (POEM). An achalasia registry was queried for patients undergoing either LHM or POEM at Baylor University Medical Center at Dallas. Patient demographics, preoperative and postoperative data points, and Eckardt scores were collected. The patients were further stratified into their follow-up intervals, immediate postoperative and long-term follow-up, to assess surgical success. A subset analysis was done for success of treatment for patients who had redo surgery versus those undergoing the procedure for the first time. There were 12 patients in the POEM group and 11 patients in the LHM group. Both groups demonstrated mean lower esophageal sphincter pressures with failure to relax. Procedure length and hospital length of stay were similar between the two groups. There were three adverse events in each group, but none altered the patient's postoperative clinical course. Eckardt scores, used to assess success of the surgery, were 82% for POEM patients and 66% for LHM patients after 6 months. The outcomes for POEM and LHM in our early experience are similar to those reported in the literature for high-volume centers managing achalasia.